Highly dynamic changes of regional HBV epidemiology over two decades - Ricco, Gabriele; Coco, Barbara; Colombatto, Piero; Oliveri, Filippo; Cavallone, Daniela; Bleve, Patrizia; Vianello, Barbara; Romagnoli, Veronica; Salvati, Antonio; Surace, Lidia; Bonino, Ferruccio; Brunetto, Maurizia Rossana (Digestive and liver disease, 2023)
HBV epidemiology is highly heterogeneous and rapidly evolving worldwide: we studied its last two-decades dynamics in a large single center cohort. In all consecutive HBsAg-positive subjects firstly admitted (2000–2019) at the Pisa-University-Hospital Hepatology-Referral-Center, demographic, virologic and clinical variables were analyzed by admission decade (2000–2009 vs 2010–2019) and origin (Italian vs non-Italian natives). Of 2003, 1878 (93.7%) subjects were eligible: 1798(95.7%) with HBV-chronic [126(7%) HDV, 72(4%) HCV, 11(0.6%) HIV co-infected] and 80(4.3%) HBV-primary infections (93.7% Italians). Among 1589(88.4%) mono-infected, 496(31.2%) were immigrants, younger than Italians [34.0(5.1–77.1)-52.5(10.0–87.2) years], with female prevalence [204/496(41.1%)-340/1093(31.1%); p<0.001] increasing overtime (14.6–45.0%; p<0.001). Italians aged across decades [50.3(11.1–87.2)-56.2(10.0–86.7) years; p<0.001], HBeAg-positivity remained stable (12.3–14.5%) and acute hepatitis increased (4.0–8.0%; p = 0.003). CHB declined [439/721(60.9%)-320/868(36.9%); p<0.001] whereas HBeAg-negative infection increased [277/626(44.2%)-538/755(71.3%); p<0.001]. Cirrhosis declined [195/721(27.0%)-125/868(14.4%); p<0.001], except in anti-HDV-patients [93/126(73.8%); 42(45.1%) non-Italians], younger than HBV-mono-infected (47.4–57.6 years; p<0.001). Effective preventive health care policies and immigration flows account for increasing prevalence of HBeAg-negative infection across the last two decades. Antiviral therapy mitigated disease progression in aging Italian CHB but not in CHD patients, mainly young immigrants, emphasizing the unmet need of effective CHD therapies; HBeAg-positive CHB and acute hepatitis B persist in non-vaccinated Italian adults, prompting vaccination in the elderly with risky behaviors.